Covid 19: Governing or the dilemma of saving life and deferring the economy or saving the economy and deferring death - del Valle, Carlos (2020)
The global health crisis generated by Covid-19 has not only had repercussions on the health of the population, because it has obvious economic, political, social and cultural implications. The foregoing leads us to reflect on the economic and political models and the way of governing, and to question how they explain the way in which this pandemic has been faced. In this same sense, it is interesting to address how in these models and in this way of governing the marginalization and exclusion of diversities increases.